2011
DOI: 10.1089/ther.2011.0002
|View full text |Cite
|
Sign up to set email alerts
|

Management of Febrile Critically Ill Adults: A Retrospective Assessment of Regional Practice

Abstract: The aim of this study was to report on fever epidemiology and management strategies within a general population of critically ill patients. This was a retrospective cohort study among febrile patients (temperature ≥38.3°C) without acute brain injury admitted to one of four regional adult intensive care units (ICUs). There were 7535 ICU admissions over the 30-month study period. One hundred patients with fever were randomly selected for detailed analysis and represent the study population. The study population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…Given that bloodstream infection can also be primary or catheter related, the bloodstream is a common site of infection in critically ill patients with pyrexia [3, 5, 19, 36]. Among patients admitted to the ICU owing to a severe bloodstream infection that is community onset, the most common pathogens are E. coli , S. aureus , and S. pneumoniae [37].…”
Section: Aetiology and Incidence Of Hyperthermia And Pyrexiamentioning
confidence: 99%
See 2 more Smart Citations
“…Given that bloodstream infection can also be primary or catheter related, the bloodstream is a common site of infection in critically ill patients with pyrexia [3, 5, 19, 36]. Among patients admitted to the ICU owing to a severe bloodstream infection that is community onset, the most common pathogens are E. coli , S. aureus , and S. pneumoniae [37].…”
Section: Aetiology and Incidence Of Hyperthermia And Pyrexiamentioning
confidence: 99%
“…However, this study probably underestimated the incidence of infectious fever because the authors did not systematically evaluate the results of diagnostic tests other than cultures for identifying infection [3]. Another study in the same health region that undertook a detailed chart review to investigate pyrexia management practices in 100 medical and surgical critically ill patients without an acute neurological condition found that infections were responsible for 73 % of pyrexia episodes, with pneumonia the most common infection, occurring in 70 % of infectious fevers [36]. This is consistent with a large, prospective study of infection occurrence in 71 ICUs in Italy, wherein the most common source of infection was pneumonia [30].…”
Section: Aetiology and Incidence Of Hyperthermia And Pyrexiamentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the use of antipyretic medications and physical cooling interventions to treat fever is widespread in clinical practice. 1-4 …”
mentioning
confidence: 99%
“…One study from Canada found that among 100 critically ill adults without acute neurological injury, 79 received pharmacologic and/or physical anti-pyretic therapy during an episode of fever [28]. Similarly, another study conducted in Japan and Korea found that more than 50% of patients admitted to ICUs were treated with temperature lowering therapy [5].…”
Section: Discussionmentioning
confidence: 99%